If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6k + -2s = 4s + -12 Reorder the terms: 6k + -2s = -12 + 4s Solving 6k + -2s = -12 + 4s Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '2s' to each side of the equation. 6k + -2s + 2s = -12 + 4s + 2s Combine like terms: -2s + 2s = 0 6k + 0 = -12 + 4s + 2s 6k = -12 + 4s + 2s Combine like terms: 4s + 2s = 6s 6k = -12 + 6s Divide each side by '6'. k = -2 + s Simplifying k = -2 + s
| 2ac-5b= | | (7x+4)=(10x-28) | | -1/6*(-9/7) | | 4y^2=5v+6 | | 15x-20=x+10 | | X+2(4x+14)=1 | | 3b^2=2b+5 | | 18x^3-12x^2/6x^2 | | 4(m+6)=48 | | 9x+18x^2=0 | | 3x-5x+5=1 | | 9b=60 | | (7+22)*8=8x | | Csquared-10c=0 | | 7+22=8x | | b=60 | | 6a+9b=4500 | | a+21=-56 | | 4[5+2(3)-3]= | | 2c=c+17 | | v=4/3pi5^3 | | 6x^5+7x= | | 12x+7=10x | | 585.00+0.13b=850.00 | | 3c=c+34 | | 585+0.13b=850 | | 1x-5+14=8 | | 1.5x-5+14=8 | | 8Z+5=6Y+3 | | p=3q^3 | | 8m+3n-4m+8n= | | 930/30000= |